A practical risk score for early prediction of neurological outcome after out-of-hospital cardiac arrest: MIRACLE2. (30th July 2020) - Pareek, Nilesh; Kordis, Peter; Beckley-Hoelscher, Nicholas; Pimenta, Dominic; Kocjancic, Spela Tadel; Jazbec, Anja; Nevett, Joanne; Fothergill, Rachael; Kalra, Sundeep; Lockie, Tim; Shah, Ajay M; Byrne, Jonathan; et al.
Abstract: Aims: The purpose of this study was to develop a practical risk score to predict poor neurological outcome after out-of-hospital cardiac arrest (OOHCA) for use on arrival to a Heart Attack Centre. Methods and results: From May 2012 to December 2017, 1055 patients had OOHCA in our region, of whom 373 patients were included in the King's Out of Hospital Cardiac Arrest Registry (KOCAR). We performed prediction modelling with multivariable logistic regression to identify predictors of the primary outcome to derive a risk score. This was externally validated in two independent cohorts comprising 473 patients. The primary endpoint was poor neurological outcome at 6-month follow-up (Cerebral Performance Category 3–5). Seven independent predictors of outcome were identified: missed (unwitnessed) arrest, initial non-shockable rhythm, non-reactivity of pupils, age (60–80 years—1 point; >80 years—3 points), changing intra-arrest rhythms, low pH <7.20, and epinephrine administration (2 points). The MIRACLE2 score had an area under the curve (AUC) of 0.90 in the development and 0.84/0.91 in the validation cohorts. Three risk groups were defined—low risk (MIRACLE2 ≤2—5.6% risk of poor outcome); intermediate risk (MIRACLE2 of 3–4—55.4% of poor outcome); and high risk (MIRACLE2 ≥5—92.3% risk of poor outcome). The MIRACLE2 score had superior discrimination than the OHCA [median AUC 0.83 (0.818–0.840); P  < 0.001] and Cardiac Arrest Hospital Prognosis models [median AUC 0.87 (0.860–0.870; P  = 0.001] and equivalent performance with the Target Temperature Management score [median AUC 0.88 (0.876–0.887); P  = 0.092]. Conclusions: The MIRACLE2 is a practical risk score for early accurate prediction of poor neurological outcome after OOHCA, which has been developed for simplicity of use on admission. Graphical Abstract: